Rapid improvements in pain and quality of life are sustained after surgery for spinal metastases in a large prospective cohort. (3rd May 2016) - Choi, David; Fox, Zoe; Albert, Todd; Arts, Mark; Balabaud, Laurent; Bunger, Cody; Buchowski, Jacob Maciej; Coppes, Maarten Hubert; Depreitere, Bart; Fehlings, Michael George; Harrop, James; Kawahara, Norio; et al.
Abstract: Introduction Metastatic spinal cancer is a common condition that may lead to spinal instability, pain and paralysis. In the 1980s, surgery was discouraged because results showed worse neurological outcomes and pain compared with radiotherapy alone. However, with the advent of modern imaging and spinal stabilisation techniques, the role of surgery has regained centre stage, though few studies have assessed quality of life and functional outcomes after surgery.Objective We investigated whether surgery provides sustained improvement in quality of life and pain relief for patients with symptomatic spinal metastases by analysing the largest reported surgical series of patients with epidural spinal metastases.Methods A prospective cohort study of 922 consecutive patients with spinal metastases who underwent surgery, from the Global Spine Tumour Study Group database. Pre- and post-operative EQ-5D quality of life, visual analogue pain score, Karnofsky physical functioning score, complication rates and survival were recorded.Results Quality of life (EQ-5D), VAS pain score and Karnofsky physical functioning score improved rapidly after surgery and these improvements were sustained in those patients who survived up to 2 years after surgery. In specialised spine centres, the technical intra-operative complication rate of surgery was low, however almost a quarter of patients experienced post-operative systemic adverse events.Conclusion Surgical treatment for spinal metastases produces rapid pain relief, maintains ambulation and improves good quality of life. However, as a group, patients with cancer are vulnerable to post-operative systemic complications, hence the importance of appropriate patient selection.